Evaluatıng Customer Perceptıons And Expectatıons Of The Servıce Qualıty Delıvery A Case Of The Cıty Of Tshwane Emergency Management Servıces Department - Shumba, Knowledge; Ebewo, Patrick; Rabalao, Rosina Tabea (Cita Konsultindo Research Center, 2024)
Emergency services are intangible, making it challenging for public agencies like the City of Tshwane Emergency Services Department (CoT's ESD) to analyse customers perceptions and assess the desired results of their service quality. The review of literature indicates limited academic attempts to evaluate expectations from customers and their perceptions in relation to customer satisfaction in the Municipal Government Emergency Services Department (CoT ESD) context, especially in South Africa. It is in this regard that the study evaluated the customer perceptions and expectations of residents regarding service quality delivery of CoT ESD. The study adopted the quantitative method with the use of self-administered questionnaire to a randomly selected sample of 274 respondents within the seven regions of the City of Tshwane. Data was analysed using the SPSS version 27. The study concludes that there is a positive relationship between customer expectations and the satisfaction; there is a positive relationship between customer perception of services delivered on services delivered by the Emergency Services Department of the City of Tshwane. The study recommends that the Emergency Services Department must remain committed to ensuring client satisfaction, which can be a part of its overall business plan